2021
DOI: 10.1016/j.eclinm.2021.101172
|View full text |Cite
|
Sign up to set email alerts
|

Community SARS-CoV-2 seroprevalence before and after the second wave of SARS-CoV-2 infection in Harare, Zimbabwe

Abstract: Background By the end of July 2021 Zimbabwe, has reported over 100,000 SARS-CoV-2 infections. The true number of SARS-CoV-2 infections is likely to be much higher. We conducted a seroprevalence survey to estimate the prevalence of past SARS-CoV-2 in three high-density communities in Harare, Zimbabwe before and after the second wave of SARS-CoV-2. Methods Between November 2020 and April 2021 we conducted a cross-sectional study of randomly selected households in three hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 19 publications
12
26
0
Order By: Relevance
“…Moreover, very high heterogeneity was noted among the included studies. However, this incidence is comparable to the 10% that has been reported elsewhere [ 39 ]. Accurate figures of incidence of infection among HCWs will be likely elusive because of different testing strategies in different countries, with some testing only symptomatic workers whilst some mandatorily test all their HCWs, and also similar to the general population, HCWs do not have uniform health seeking behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, very high heterogeneity was noted among the included studies. However, this incidence is comparable to the 10% that has been reported elsewhere [ 39 ]. Accurate figures of incidence of infection among HCWs will be likely elusive because of different testing strategies in different countries, with some testing only symptomatic workers whilst some mandatorily test all their HCWs, and also similar to the general population, HCWs do not have uniform health seeking behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…As an example, in a seroprevalence study in the general population in Zimbabwe, the seroprevalence was 19% (95% CI 15.1–23.5%) while the same was 53.0% (95% CI 49.6–56.4) in 2021; however, more than 50% of the patients had not reported any symptoms in the preceding six months [ 22 ]. In a meta-analysis of seroprevalence studies carried out in South America, a pooled estimate of 33.6% (95% CI 28.6–38.5%) was obtained; however, there were marked variations between studies, with seroprevalences as low as 70% in some settings [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown significant temporal and spatial heterogeneity in the pattern of infections in Kenya, [2][3][4][5][6] but these studies had the limitation of not being population-based, instead relying on convenience samples of special population groups such as blood donors, 2,6 antenatal clinic (ANC) attendees, 5 truck drivers 4 and health care workers (HCW). 3 A similar situation obtains in many low and middle income countries (LMICs), with only a handful of published population based studies having been conducted in Africa, [7][8][9][10][11] which is home to over one billion people.…”
Section: Introductionmentioning
confidence: 78%